Assessing the quality of life among children with cochlear implants in Saudi Arabia - Faisl Alqraini (PLoS ONE, 2026)
Cochlear implantation has emerged as a transformative intervention for children with severe-to-profound hearing loss, improving not only auditory and linguistic abilities but also broader aspects of quality of life. This study examined school readiness in toddlers and preschool-aged children with cochlear implants in Saudi Arabia and explored the role of psychosocial factors—self-reliance, well-being and happiness, and social relationships—in predicting readiness outcomes. Using a cross-sectional correlational survey design, data were collected from 155 parents via an online questionnaire distributed in social media groups for families of children with hearing loss. Data were collected using an online parent-reported questionnaire disseminated through established WhatsApp and Telegram groups for families of children with hearing loss in Saudi Arabia. A non-probability convenience sampling technique was employed to recruit participants. Descriptive statistics indicated that most children were perceived as keeping pace with peers in educational settings, although parental concerns about future school placement were common. Pearson correlations revealed moderate positive associations between each psychosocial factor and school readiness, while multiple regression analysis identified social relationships as the only significant predictor when all factors were considered together. The findings underscore the importance of fostering strong peer and teacher relationships in early intervention programs, alongside promoting self-reliance and emotional well-being. These results have implications for educators, policymakers, and rehabilitation specialists seeking to enhance the educational readiness and quality-of-life outcomes of children with cochlear implants in Saudi Arabia.